Evaluasi software aplikasi Senayan Library Management System (SLIMS) di lingkungan Universitas Lancang Kuning Pekanbaru menggunakan pendekatan ISO 9126 Usability - Dwiyantoro Dwiyantoro (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This research focuses on evaluating Senayan library management system (Slims) application software in the Lancang Kuning University environment using the ISO 9126.1 Usability approach. Research related to evaluation or application quality testing has been done a lot but for the evaluation of slims software in the Lancang Kuning University environment has never been done. In this research the method used is descriptive quantitative. With the method of collecting observation data, distributing questionnaires, and interviews. The sample in this study were 7 respondents from different libraries who used the slims application. Data analysis was performed using a Likert scale percentage formula. The results of this study indicate that based on the percentage of data using ISO 9126.1 usability on each attribute, namely Understandability with a percentage value of 116 predicate strongly agree, Learnability with a percentage value of 137 predicate agree, Opportunity with a value of 349 predicate strongly agree, Attactiveness with a value of 115 predicate strongly agree, and Usability Compliance with a rating of 115 is very much in agreement. From the results explained above, it can be concluded that Slims meet ISO 9126.1 usability standards.